Exchange Rate Volatility in Bangladesh: An Exploration of the Leverage Effect of Positive and Negative Economic News - Monir, Mostafa; Hasanat, Mohammad Asrarul; Islam, Jahedul; Sayem, S M (South Asian Journal of Social Sciences and Humanities, 2025)
Purpose of the Study: This research investigates the impact of leverage on exchange rate  fluctuations in Bangladesh, with a specific focus on assessing whether negative news about  the exchange rate generates a greater effect on volatility compared to positive news. Methodology: The study employs the Exponential Generalized Autoregressive Conditional  Heteroskedasticity (EGARCH) (1,1) model to analyze monthly BDT/USD exchange rate data  from January 1982 to May 2022. This approach captures the autoregressive conditional  heteroskedasticity in the data, allowing for the assessment of volatility patterns in response to  positive and negative shocks. Main Findings: The results reveal that positive shocks  generate higher volatility in the BDT/USD exchange rate compared to negative shocks,  contrary to conventional financial market expectations. Additionally, the study identifies a  reversed leverage effect, where positive return changes lead to greater volatility than  declining prices, challenging the typical pattern observed in financial markets. Applications  of This Study: The findings have significant implications for policymakers, investors, and  financial analysts. Understanding the asymmetric effects of exchange rate shocks can aid in  designing more effective risk management strategies, monetary policies, and investment  frameworks, particularly in emerging markets with volatile currencies. Novelty: This study  contributes to existing literature by uncovering a reversed leverage effect in the BDT/USD  exchange rate, which contrasts with standard financial market behavior. The application of  the EGARCH (1,1) model to a long-term dataset provides new insights into the dynamics of  exchange rate volatility and its response to macroeconomic shocks.
Keywords: Exchange rate; Volatility; GARCH; TGARCH; EGARCH; Leverage effect; Bangladesh